THE EFFECT OF USING DIGITAL DIORAMA ON STUDENT’S SPEAKING SKILL PERFORMANCE - Silvi Listia Dewi; Chalil As’ari; Intan Zuhra (LPPM Institut Pendidikan Nusantara Global, 2023)
English Education Study Program FKIP Almuslim University's third-semester students sometimes have trouble speaking the language. This is brought on by a fear of making a mistake, a lack of language knowledge, and a poor grasp of pronunciation. By utilizing effective and engaging teaching strategies and media, lecturers in the Speaking course must assist their students in resolving this issue. Diorama, particularly digital diorama, is an effective teaching tool because it is a specific three-dimensional media that illustrates or explains anything in miniature. This research was to find how the effect of using diorama in teaching students’ speaking skill ability in increasing students’ speaking skill ability. The population of these study students of in third semester of English Education Study Program of FKIP Almuslim University with 15 students. In order to see the students’ improvement on speaking skill, the procedure of quantitative data with analytic scoring rubric formulated by Oller (1979). This is the one group pre-test and post-test. The pre-test was used for knowing the skill of the students before use diorama activities. After giving the treatment, the students got the post test. The one-tailed paired-samples t-test was used to examine the effect of using diorama in teaching students’ speaking skill ability in increasing students. This result showed that digital diorama model influenced the enhancement of speaking skill after being trained with using digital diorama model.